If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 4(3x + -3) Reorder the terms: -3 + 8x = 4(3x + -3) Reorder the terms: -3 + 8x = 4(-3 + 3x) -3 + 8x = (-3 * 4 + 3x * 4) -3 + 8x = (-12 + 12x) Solving -3 + 8x = -12 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -3 + 8x + -12x = -12 + 12x + -12x Combine like terms: 8x + -12x = -4x -3 + -4x = -12 + 12x + -12x Combine like terms: 12x + -12x = 0 -3 + -4x = -12 + 0 -3 + -4x = -12 Add '3' to each side of the equation. -3 + 3 + -4x = -12 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = -12 + 3 -4x = -12 + 3 Combine like terms: -12 + 3 = -9 -4x = -9 Divide each side by '-4'. x = 2.25 Simplifying x = 2.25
| 1+(1+f)= | | 1058+44.50-x=1000 | | 12+(-20)= | | (3k)(2)= | | 1-6x=-6(x-9) | | 6(x-4)=6x | | 9x+3x-2=5x-5 | | 2x^2+24=16x | | 5(5h)= | | -35=5h+1 | | 4(1-5x)=124 | | 4(2+5k)= | | 6x+5-4x=x-1 | | 7-4y=-2y+4-2y | | 5(2+5t)= | | (4+f)+4= | | 3x-2-5x=4-x | | 12-20= | | (2+t)+2= | | (j+3)+3= | | 0=-3x^2-24x+11 | | A=x-y-1 | | (5d)(2)= | | 12+8=2x | | 5x-(2x+6)=4x-29 | | 4(2+5u)= | | -11(7+x)+9=1-6(x-1) | | P-16=-23 | | 3x+72-x=11x+9 | | 4(2+2m)= | | 21-3(2-x)=-6 | | 2(4+6v)= |